Treatment of pneumothorax and bronchopleural fistula by extracorporeal membrane oxygenation in a neonate: a case report - Zhang, Taining; Wang, Jianxiu; Zhou, Bingyin; Yan, Bin; Chen, Xilong; Wang, Yanxia; Wang, Weikai (Frontiers in Pediatrics, 2024)
Intractable pneumothorax secondary to bronchopulmonary fistula is a rare complication in neonates. We present the first report of a newborn with spontaneous pneumothorax and bronchopleural fistula treated with extracorporeal membrane oxygenation (ECMO). Positive pressure mechanical ventilation resulted in persistent air leakage from the bronchopleural fistula. When ECMO was initiated, a “total lung rest” ventilation strategy was used to facilitate the healing of bronchopleural fistula and the absorption of the pneumothorax. ECMO is an effective supportive therapy for neonate pneumothorax and bronchopulmonary fistula when conventional ventilation management fails.